Holographic Data Coding: Benchmarking and Extending HEVC With Adapted Transforms - Peixeiro, Jose Pedro; Brites, Catarina; Ascenso, Joao; Pereira, Fernando (IEEE transactions on multimedia, 2018)
Holography is an emerging technology to represent and display visual information with high expectations in terms of user experience. A hologram is a reproduction of a light field represented through the interference pattern between two wavefields the reference and the object wavefields. Whatever their creation process holograms may have a digital representation using some appropriate format. Moreover considering the huge amounts of data involved digital holographic data have to be compressed using appropriate coding solutions for example available image coding standard solutions or efficient extensions of them. In this context this paper contributes to advance the state-of-the-art on holographic data coding by: 1) benchmarking the most relevant available image coding standard solutions when using the most relevant holographic data representation formats; 2) proposing a novel mode depend directional transform-based HEVC coding solution trained with holographic data. Experimental results obtained under meaningful test conditions show that the proposed coding solution outperforms the state-of-the-art HEVC coding standard for specific formats and conditions. Altogether these two contributions are critical to understand the current status quo and advance the state-of-the-art on holographic data coding.